1997
DOI: 10.1111/j.1432-1033.1997.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bioactive Conformation of Neuropeptide Y Analogues at the Human Y2‐Receptor

Abstract: Several attempts to investigate the bioactive conformation of neuropeptide Y have been made so far. As cyclic peptides are much more rigid than linear ones, we decided to synthesise cyclic analogues of the C-terminal dodekapeptide amide neuropeptide Y Ac-25-36. Cyclisation was performed by side chain lactamisation of ornithine or lysine and glutamic or aspartic acid. The affinity of the 19 peptides ranged from K, 0.6 nM to greater than 10000 nM. We found that the size, position, orientation, configuration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…It was concluded that high affinity is correlated with a tight hairpin, where the N-and C-terminal ends are very close to each other. In contrast, a more open conformation is characterized by minor affinity [88]. This suggests that the bioactive conformation of the ligand at the Y 2 -receptor should consist of a tightly closed structure in which the N-and C-terminal parts are close and oriented to each other in a well-defined way.…”
Section: The Y 2 -Receptor N-terminally Truncated Segmentsmentioning
confidence: 87%
See 1 more Smart Citation
“…It was concluded that high affinity is correlated with a tight hairpin, where the N-and C-terminal ends are very close to each other. In contrast, a more open conformation is characterized by minor affinity [88]. This suggests that the bioactive conformation of the ligand at the Y 2 -receptor should consist of a tightly closed structure in which the N-and C-terminal parts are close and oriented to each other in a well-defined way.…”
Section: The Y 2 -Receptor N-terminally Truncated Segmentsmentioning
confidence: 87%
“…In order to stabilize the conformation of the Cterminal dodecapeptide 25 -36 of NPY, Rist and coworkers [88] introduced a lactam bridge of the type i− i+4 and varied its position along the sequence (from i= 25 to i =28) as well as its orientation (CO NH or NH CO) and size (Lys/Glu or Orn/Asp) ( Table 2). The two most potent ligands at the Y 2 -receptor, corresponding to the lactamizations Glu 27 -Lys 31 and Lys 28 -Glu 32 , showed an affinity of 0.8 and 0.6 nM, respectively.…”
Section: The Y 2 -Receptor N-terminally Truncated Segmentsmentioning
confidence: 99%
“…The ability of NPY to bind to so many different receptor subtypes can be explained by its high molecular flexibility. An attempt of investigating the local structural features that distinguish the bioactive conformations of NPY at the different receptors has been performed in our group some years ago 99, 100. The structural freedom of the C‐terminal dodecapeptide was restricted by cyclization.…”
Section: Interaction Between Ligand and Receptormentioning
confidence: 99%
“…These SK-N-MC cells selectively expresses one kind of NPY receptors which was shown to be the Y1 receptor [7,8]. Furthermore, these cells are frequently used to investigate binding as well as signal transduction of neuropeptide Y [9].Internalization studies are based on the distinction between the cell surface associated ligand and the ligand within the cell. Intact living cells are incubated with the labeled ligand at a temperature between 30 and 37 8C.…”
mentioning
confidence: 99%
“…These SK-N-MC cells selectively expresses one kind of NPY receptors which was shown to be the Y1 receptor [7,8]. Furthermore, these cells are frequently used to investigate binding as well as signal transduction of neuropeptide Y [9].…”
mentioning
confidence: 99%